2015
DOI: 10.1002/jpln.201400288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different macronutrient cation ratios on macronutrient and water uptake by melon (Cucumis melo) grown in recirculating nutrient solution

Abstract: The aim of the present study was to determine uptake ratios between macronutrients and water for melon (Cucumis melo L. cv. Dikti) grown in a closed soilless cropping system. The obtained data can be used to establish standard nutrient solution compositions for melon crops grown in closed hydroponic systems under Mediterranean climatic conditions. Nutrient and water uptake by plants in the closed hydroponic system was compensated for by supplying replenishment nutrient solutions (RNS) differing either in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 32 publications
3
25
0
10
Order By: Relevance
“…Moreover, the reduction in NO3 − , H2PO4 − and K + concentrations in the drainage waters applied for irrigation compared to the nutrient solution could be related to the melon nutrient uptake. Our results were similar with the findings reported by Neocleous and Savvas [26] in the same crop.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the reduction in NO3 − , H2PO4 − and K + concentrations in the drainage waters applied for irrigation compared to the nutrient solution could be related to the melon nutrient uptake. Our results were similar with the findings reported by Neocleous and Savvas [26] in the same crop.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the reduction in NO 3 − , H 2 PO 4 − and K + concentrations in the drainage waters applied for irrigation compared to the nutrient solution could be related to the melon nutrient uptake. Our results were similar with the findings reported by Neocleous and Savvas [26] in the same crop. The irrigation with sequential reuse water against standard nutrient solution resulted in an increase of grey water which may be dangerous from an environmental point of view as suggested by Castellanos et al [27], while the irrigation with blended drainage water against standard nutrient solution resulted in an increase of blue water which is a great drawback in areas with water scarcity as mentioned also by Hoekstra et al [28].…”
Section: Discussionsupporting
confidence: 93%
“…In tomato production, high-EC induced inhibition of Ca absorption is very common in substrate cultivation, which often leads to BER of tomatoes due to Ca deficiency ( Uozumi et al, 2012 ). In this study, as EC in root-zone solution increased gradually during the growing period ( Figure 1 ), BER increased gradually for all substrates from 3rd to 13th trusses ( Table 3 ), indicating the Ca deficiency induced by high EC ( Neocleous and Savvas, 2015 ). This result suggested that inhibition of Ca deficiency was still a challenge for soilless tomato production.…”
Section: Discussionmentioning
confidence: 53%
“…Despite this, PVC cultivation generally showed the lowest BER ( Table 3 ). This phenomenon could be explained by the fact that (1) peat contained high content of Ca ( Table 1 ) and was able to enhance Ca absorption by tomato crops ( Zhang et al, 2015 ), (2) lower K + /Ca 2+ ratio in root-zone solution under PVC (Supplementary Figure S1 ) reduced K-Ca antagonism in root-zone ( Neocleous and Savvas, 2015 ) and (3) the relatively high buffer ability of peat-vermiculite (PVC) resulted in a relatively stable pH during the growing period ( Figure 1 ) and benefited Ca uptake by tomato crops ( Rippy, 2005 ). Despite the benefits of PVC, no statistical difference in total BER was found between CC and PVC ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, plants in early stages of growth showed increased needs for nutrients compared to the relative water needs, thus, UCs were initially higher than subsequent estimates as the crop aged. This could be explained by the fact that young plants have an increased need for nutrients due to rapid growth, while their water requirements are still small at the same time ( Neocleous and Savvas , ). It is well known that under saline conditions Cl − restricts NO3 - uptake ( Grattan and Grieve , ).…”
Section: Discussionmentioning
confidence: 99%